# Inner Product Space

## Inner Product Space :

Let $U$ and $V$ be any two inner product spaces over the same field $\mathbb{R}$ and $T:U\to V$be a linear transformation then we say that T preserves inner product if
(1) T is orthogonal transformation
i.e. $\langle T_\alpha, T_\beta \rangle=\langle \alpha, \beta \rangle$
(2) $\|T_\alpha\|=\|\alpha\| , \forall \ \alpha\in U$
(3)  T preserves isometry.
i.e. $\|T_\alpha-T_\beta\|=\|\alpha-\beta\| , \forall \ \alpha, \beta \in U$

## Theorem :

Let $V$ be a m-dimensional inner product space over $\mathbb{R}$ and $T:U\to V$ be a linear transformation then show that following statements are equivalent:
(1) T is orthogonal.
(2) $\|T(x)\|=\|x\|$
(3) $\{e_i\}_{i=1}^{n}=\{e_1, e_2, ... , e_n\}$ is orthogonal basis of $V$ then $\{T_{e_i}\}_{i=1}^{n}$ is also orthogonal basis of $V$.

## Proof :

First we will prove that $(1)\implies (2)$
Assume that $T$ is orthogonal.
i.e. $\langle T_x, T_y \rangle=\langle x, y \rangle$, $\forall \ x, y\in V$
Consider, $\|T_x\|=\sqrt{\langle T_x, T_x \rangle}$      ... by definition of norm.
$=\sqrt{\langle x, x \rangle}$     $\because T$ is orthogonal.
$=\|x\|$
$\therefore \|T_x\|=\|x\| , \forall \ x \in V$
i.e. $(1)\implies (2)$ is proved.
Now we will prove that, $(2)\implies (1)$
Assume that $\|T_x\|=\|x\| , \forall \ x \in V$
To prove that $T$ is orthogonal.
i.e. $\langle T_x, T_y \rangle=\langle x, y \rangle$, $\forall \ x, y\in V$
Since, $V$ is real inner product space,
$\implies x+y \in V$
$\implies \|T(x+y)\|=\|x+y\|$    .....      $\because x+y \in V$
$\implies \|T_x+T_y\|=\|x+y\|$ ......       $\because$ T is linear.
$\implies \|T_x+T_y\|^2=\|x+y\|^2$
$\implies \langle T_x+T_y, T_x+T_y \rangle=\langle x+y, x+y \rangle$   By def. of norm.
$\implies \langle T_x, T_x \rangle +2\langle T_x, T_y \rangle + \langle T_y, T_y \rangle=\langle x, x \rangle +2\langle x, y \rangle + \langle y, y \rangle$
$\implies \|T_x\|^2+2\langle T_x, T_y \rangle + \|T_y\|^2=\|x\|^2+2\langle x, y \rangle +\|y\|^2$
As $x, y \in V \implies \|T_x\|^2=\|x\|^2$ & $\|T_y\|^2=\|y\|^2$
$\therefore 2\langle T_x, T_y \rangle=2\langle x, y \rangle$
$\therefore \langle T_x, T_y \rangle=\langle x, y \rangle$
Thus, $\langle T_x, T_y \rangle=\langle x, y \rangle$, $\forall \ x, y\in V$
$\implies$ T is orthogonal.
Now, to prove that $(1) \implies (3)$
Suppose T is orthogonal. i.e. $\langle T_x, T_y\rangle =\langle x, y\rangle, \forall \ x, y\in V$
If $\{e_i\}_{i=1}^{n}$ is orthonormal basis of V then we have to prove that $\{T_{e_i}\}_{i=1}^{n}$ is also an orthonormal basis of V.
As $\{e_i\}_{i=1}^{n}$ is orthogonal $\implies \langle e_i, e_j \rangle= 1$,   if $i=j$.
$=0$,   if $i\ne j$
and $\{e_i\}_{i=1}^{n}$ basis of V $\implies$ dim $V=n$.
Now, $\langle T_{e_i}, T_{e_j}\rangle=\langle e_i, e_j \rangle$, $\because$ T is orthogonal.
$=1$, if $i=j$
$=0$, $i\ne j$
$\therefore \langle T_{e_i}, T_{e_j}\rangle=1$, if $i=j$
$=0$, if $i\ne j$
$\therefore \{T_{e_i}\}_{i=1}^{n}$ is orthonormal.
Every orthonormal set is linearly independent $\implies \{T_{e_i}\}_{i=1}^{n}$ is linearly independent.
As dim $V=n=$ No. of elements in $\{T_{e_i}\}_{i=1}^{n}$,
$\implies \{T_{e_i}\}_{i=1}^{n}$ is maximal linearly independent subset of V.
By theorem which states that every maximal linearly independent subset of vector space forms a basis of that vector space.
$\therefore \{T_{e_i}\}_{i=1}^{n}$ is orthonormal basis of V.
Now, to prove that $(3) \implies (1)$
Consider $\{e_i\}_{i=1}^{n}$ is orthonormal basis of V and $\{T_{e_i}\}_{i=1}^{n}$ is also an orthonormal basis of V.
We have to prove that T is orthogonal.
i.e. $\langle T_x, T_y \rangle=\langle x, y \rangle, \forall \ x, y \in V$
Let x, y be any two arbitrary elements of inner product space V.
$\implies x=\sum_{i=1}^{n}{x_ie_i}$ & $y=\sum_{j=1}^{n}{y_je_j}$  ($\because \{e_i\}_{i=1}^{n}$ is basis of V)
$T_x=\sum_{i=1}^{n}{x_iT_{e_i}}$ & $T_y=\sum_{j=1}^{n}{y_jT_{e_j}}$
Consider, $\langle x, y\rangle=\langle\sum_{i=1}^{n}{x_ie_i}, \sum_{j=1}^{n}{y_je_j} \rangle$
$=\sum_{i,j=1}^{n}{x_iy_j}\langle e_i, e_j \rangle$
$=\sum_{i,j=1}^{n}{x_iy_j}$
Now,
$\langle T_x, T_y \rangle=\langle \sum{x_iT_{e_i}}, \sum{y_jT_{e_j}} \rangle$
$=\sum{x_iy_j}\langle T_{e_i}, T_{e_j} \rangle$
$=\sum_{i,j=1}^{n}{x_iy_j}$
$\therefore \langle T_x, T_y \rangle=\langle x, y \rangle, \forall \ x, y \in V$
Since, $(1)\iff (2)$ and $(1)\iff (3)$
$\therefore$ above all statements are equivalent.